Clinical Insights into Protein-based Therapies for Precision Targeting of Psoriasis - Yadav, Krishna; Vijayalakshmi, R.; Sahu, Kantrol Kumar; Sucheta; Nagori, Kushagra; Singh, Deependra; Singh, Manju Rawat; Pradhan, Madhulika (Recent Advances in Inflammation & Allergy Drug Discovery, 2025)
Psoriasis (PsR), a chronic autoimmune disorder, affects millions of individuals globally and has a substantial impact on their quality of life. This complex condition involves intricate molecular networks and signaling pathways, making the development of effective treatments a significant challenge. Moreover, to advance treatment options, precise targeting of cells through the identification of protein biomarkers in PsR has emerged as a promising field of research for both fundamental and clinical scientists. These protein components provide valuable insights into the underlying mechanisms of the disease and can serve as indicators of treatment response. Furthermore, by identifying specific biocomponents, researchers can develop targeted therapeutics that address the molecular abnormalities driving PsR. The use of biologics as potential targets for improving treatment efficacy is a significant focus in PsR research. Biologics, which include monoclonal antibodies and fusion proteins, specifically target key molecules involved in the immune response, such as tumor necrosis factor-alpha (TNF-α) and interleukins (IL). These targeted therapies have demonstrated substantial efficacy in managing PsR by modulating the immune system and reducing inflammation. Recent advancements in molecular-targeted therapies utilizing biologics or small-molecule inhibitors have contributed to improving patient outcomes. This review aims to summarize the recent discoveries and insights regarding biocomponents and their importance in treating PsR, encompassing both its inflammatory and dermatological aspects. Furthermore, the review discusses the commercial outcomes of ongoing clinical trials for various biological-based therapeutic modalities for PsR, providing valuable insights into the evolving landscape of PsR therapeutics. These developments indicate the growing interest and investment in improving treatment options for individuals living with PsR.
Keywords: Psoriasis